(3GJaGbjGJ efXeI GdJLGQI GdYGdejI (B:s (3GdeWGdH hGdENJdGdGJ hGdJZjQGJ GddGReI (B/s - (3dGd OGS, HgGLjQGKs; (3YHO GdSdGe, QVG s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 2005)
(3GdENJdGdGJ GdQFjSjI aj fJGFL LhdI GdChQLhGj(B- (3eSCdI GfbGP GdMbhb hGdEdJRGeGJ(B- (3GdfaGP Gdi GdShb(B- (3GdJOGHjQ GdJLGQjI GdWGQFI(B- (3JOGHjQ aj ehGLgI GdeeGQSGJ GdJLGQjI Zj GdYGOjI(B- (3GJaGbjGJ aj bWGYGJ HYjfgG(B- (3eSGFd JbdjOjI(B- (3HYV GdbhGYO GdCNQi(B- (3edNU dCge GdeXGgQ GdELGHjI hGdeKGdH hGdJZjQGJ(B.s
Keywords: (3GdEJaGbjGJs; (3efXeI GdJLGQI GdYGdejIs